Prospek Budidaya Ikan Paitan (Mystacoleucus marginatus) pada Rawa Gambut di Gampong Jeumpheuk Kecamatan Sampoiniet Kabupaten Aceh Jaya - Akhmad Baihaqi; Yusya Abubakar; Heru Prono Widayat; Bagio Bagio; Ahmad Humam Hamid (Jurnal Pengabdian Agro and Marine Industry, 2022)
Paitan fish (Mystacoleucus marginatus) cultivation is an effort to utilize peat swamps that have economic prospects and support ecosystem conservation. Paitan fish thrive in fresh to brackish water. This fish is in demand by the coastal communities of Aceh Jaya to Singkil. The activity method uses discussion and counseling for farmers and fishermen in Jeumpheuk Village. The target of the activity is the performance of economic analysis of Paitan fish farming in peat waters so that it can be applied to increase family income. The results of the simulation activity obtained that the production cost of the cage system Paitan fish farming was IDR 4,164,600,-. The yield is estimated at 123 kg/harvest season with a selling price of IDR 72,000 and an income of IDR 8,832,000. The revenue is IDR 4,667,400/harvest season, the R/C ratio is 1.12, BEP production is 57.84 kg, and the BEP price is IDR 33,951/kg.